School Performance Measurement Based on Business Architecture - Shabrina, Idzni; Prahastina, Rista; H., Fifit Yulianti Amanah; Yaqin, Muhammad Ainul (Proceeding International Conference on Science and Engineering, 2020)
School performance measurement is the process of collecting, processing, analyzing and interpreting data about the quality of work carried out by school members in carrying out their main tasks and roles. Measuring the performance of an organization will encourage the achievement of objectives in the organization. A performance measurement system must be built so that the information obtained is as much and as accurate as possible. Business architecture is a formal representation and tools as well as information for business professionals in assessing, changing and designing a business. Business modeling will show the relationship of organizational behavior with the information needed, and the relationships that occur within the organizational structure, so that business architecture is the main thing that must be completely defined before continuing on to the next stage. To encourage schools to achieve goals and design business strategies that are in line with the objectives, this research will propose a system for measuring school performance based on business architecture.